Determinants of community-based health insurance implementation in west Gojjam zone, Northwest Ethiopia: a community based cross sectional study design - Tsega Hagos Mirach; Getu Debalkie Demissie; Gashaw Andargie Biks (BMC, 2019)
Abstract Background In most developing countries, healthcare cost is mainly paid at the time of sickness and out-of-pocket at the point of service delivery which potentially could inhibit access. The total economic cost of illness for households is also estimated to be frequently above 10% of household income which is categorized as catastrophic. The purpose of this study was to assess factors that determine decisions to join the community based health insurance in West Gojjam zone. Methods A community based cross sectional survey was conducted to collect data from 690 household heads using a multistage sampling technique. A binary logistic regression was used to identify the determinants of household decisions for CBHI enrollment. Results Out of the participants, 58% were CBHI members. Besides, family size (AOR = 1.17; CI = 1.02-1.35), average health status (AOR = .380; CI = .179-.805), chronic disease (AOR = 3.42; CI = 1.89-6.19); scheme benefit package adequacy (AOR = 2.17; CI = 1.20-3.93), perceived health service quality (AOR = 3.69; CI = 1.77-7.69), CBHI awareness (AOR = 4.90; CI = 1.65-14.4); community solidarity (AOR = 3.77; CI = 2.05-6.92) and wealth (AOR = 3.62; CI = 1.67-7.83) were significant determinant factors for enrolment in the community based health insurance scheme. Conclusion CBHI awareness, family health status, community solidarity, quality of service of health institutions, and wealth were major factors that most determine the household decisions to enroll in the system. Therefore, in-depth and sustainable awareness creation programs on the scheme; stratified premium- based on economic status of households; incorporation of social capital factors, particularly building community solidarity in the scheme implementation are vital to enhance sustainable enrollment. As perceived family health status and the existence of chronic disease were also found significant determinants of enrollment, the Government might have to look for options to make the scheme mandatory.